Implant sonication versus intraoperative tissue sample cultures for Periprosthetic Joint Infection (PJI) of Shoulder Arthroplasty - Padolino, Antonio; Cataldo, Giacomo; Tarallo, Luigi; Fabbri, Elisabetta; Merolla, Giovanni; Micheloni, Gian Mario; Paladini, Paolo; Porcellini, Giuseppe (Acta Biomedica Atenei Parmensis, 2021)
Introduction Periprosthetic joint infection (PJI) is the most problematic complications after shoulder arthroplasty. Many diagnostic tools have been identified to find infection, such as hystopatologic examination of tissue sections or cultures of intraoperative tissue. Implant sonication fluid culture showed good results in order to enhance diagnostic accuracy, but literature results are still controversial. Aim of our study is to compare the results of sonication with intraoperative tissue sample cultures. Patients and Methods From February 2016 to January 2018 we performed 102 revisions of Total Shoulder Arthroplasty (TSA) for suspected PJI. Sixty - five patients respected the criteria for admission to the study. In each case periprostethic specimens were collected and explanted prosthesis were put inside sterile fluid, sonicated and then placed under culture. Results Among the sixty-five patients, 36 were considered as possible, probable or certain infection. Tissue cultures were positive for infection in thirty - four cases (52,3%) and in nineteen cases was found the positivity for Cutibacterium acnes. Sonication fluid cultures were positive in forty cases (61,5%), with a positivity for Cutibacterium acnes in twenty - seven cases. The sensitivities of sonication and tissue cultures for the diagnosis of shoulder PJI were 83.3% and 88,9% (P = 0,08); the specificities were 65.5% and 93,1% (P < 0.01) respectively. Conclusion Our results suggest that sonication technique had not shown a clear advantage in postoperative shoulder PJI diagnosis, but it’s a real aid to detect Cutibacterium acnes. In any case, sensitivity and mostly specificity were higher with tissue cultures.